Impact Evaluation of Calcium and Vitamin D Supplementation and Physical Activity on Bone Health Status of Elderly Population of Urban Vadodara - Annapurna Maity; Komal Chauhan; Nishita Panwar; Pooja Mistry (Journal of Pharmacy and Nutrition Sciences, 2015)
Background: Osteoporosis is a global public health problem affecting the ageing population and influenced by poor nutrition, lack of physical activities, and absence of supplementation on time. Objectives: To study the impact of Calcium and vitamin D supplementation along with weight bearing exercises on bone health status of elderly. Methods:30 elderly males and 20 elderly females having poor BMD and poor serum vitamin D were supplemented with 1000 mg calcium and 500 IU vitamin D/ day along with weight bearing exercises for a period of 3 months, along with that 60000 IU vitamin D3/week for 2 months were given to 30 males only. Serum calcium, Vitamin D, BMD, dietary calcium intake, frequency of vitamin D rich food intake, anthropometry etc. were measured at the baseline as well as after the intervention. Results: Mean BMD T-scores (-1.1 to -2.5: osteopenia; >-2.5: osteoporosis) of the elderly males and females were significantly (p?0.001) decreased after the intervention depicting improvement (baseline:-2.34±0.50, final:-1.86±0.61). 26.7% reduction in osteoporotic cases among males and 50 % among women was achieved. Mean serum calcium (baseline: 9.38±0.63, final: 9.46±0.61) and vitamin D level (baseline: 23.76±13.17, final: 35.48±14.84) was increased significantly (p?0.05). 60% males and 70% females achieved vitamin D sufficiency level after the intervention. Mean physical endurance (Grip strength, standing balance, walking speed and rise from chair) scores were significantly increased in both males and females. Locomotor problems were reduced among 6.7% males and 40% females after regular weight bearing exercise and supplementation. Conclusion:Calcium and vitamin D supplementation with daily weight bearing exercise has a preventive and curative effect on BMD and it maintains the serum calcium and vitamin D levels. Long term and high dose supplementation needs further investigation.